CORRELATION BETWEEN GRAMMAR MASTERY AND READING COMPREHENSION OF THE STUDENTS IN STIE INDONESIA PONTIANAK - Negara, Irma Manda (IKIP PGRI Pontianak, 2016)
This study aims to investigating on the correlation between students grammar mastery and their ability in reading comprehension in STIE Indonesia Pontianak. This was quantitative research applied ex post factodesigns. The population of this study was the first semester students of STIE Indonesia Pontianak. The researcher used sample consist of 41 students. The instrument of this research was in the form of grammar mastery test and reading comprehension test. The data collected were analyzed by means of the descriptive techniques and using Pearson Product Moment Correlation. The results of the descriptive analysis are as follows: (1) there are 16 students or 39,02% got scores 40 - 59. This means that there is still a lack of grammar mastery of the students first semester STIE Pontianak in academic year 2016/2017 and value of the average (mean) is 60,68 based classification categories, it in the category of fair; (2) there are 16 students or 39,02% got scores 40 - 59. This means that there is still a lack of reading comprehension of the students first semester STIE Pontianak in academic year 2016/2017 and value of the average (mean) is 58,83 based classification categories, it in the category of less. The results of the Pearson Product Moment Correlation found that there is a significant correlation between students of grammar mastery and the students abilityÂ in reading comprehension with a correlation coefficient was 0,970; t-counted is 24,9 and the relationship between grammar maastery and reading comprehension can be concluded in the category of very high.Â Keywords: correlation, grammar mastery, reading comprehension.